Fractal Patch Antenna based on Crystal Photonic applied to Intelligent Transportation Systems in the 40 GHz Millimeter Waveband - Bagheri, Nila (2023)
5G (and beyond) has very high bandwidth, short latency, better quality of service, and the right amount of capacity. Technological breakthroughs in mobile communication systems user equipments operating in the millimeter wavebands imply a high gain to compensate the effect of path loss. In this work, a novel photonic crystal-based microstrip patch antenna array with high gain is designed to be used in the next generation intelligent transportation ssytems, e.g., V2X, and other exciting applications. The Photonic Band Gap (PBG) structure and Finite Element Method were considered. By using the High Frequency Structure Simulation (HFSS) software, a fractal microstrip patch antenna operating in the U-band of the electromagnetic spectrum is conceived and modeled on a two-dimensional photonic crystal. The use of the PBG structure improves the antenna’s gain and bandwidth, while the antenna’s fractal form decreases its size and improves its input impedance. The operational frequency range is 41.72-45.12 GHz with a resonant band centered at 43.26 GHz. The proposed antenna is comprised of a 0.45 mm thick copper ground plane, a 0.9 mm thick FR-4 epoxy substrate with a relative transmittance of 4.4, and a 0.45 mm thick copper antenna patch. The achieved frequency band gain is 8.95 dBi.